Curing mechanism of resole phenolic resin based on variable temperature FTIR spectra and thermogravimetry-mass spectrometry. (19th May 2022) - Hu, Honglin; Wang, Wei; Jiang, Liqin; Liu, Liang; Zhang, Ying; Yang, Yunhua; Wang, Jinming
To solve the problem that the curing mechanism evolution of phenolic resin catalyzed by Ba(OH)2 remained unclear, the p-p methylene index, o-p methylene index, o-o methylene index, hydroxymethyl index, and ether index were introduced to quantitatively investigate the chemical structure of resin in the curing temperature range of 90–230°C. The chemical structures were investigated by variable temperature FT-IR. The gas products released with the increase of curing temperature were characterized by Thermogravimetry-Mass Spectrometry. The curing mechanism from 90°C to 230°C was concluded finally. The results show that the main reaction is the formation of the p-p methylene group in the range of 90–120°C. It is difficult to form the o-p methylene bridge at this stage. In the range of 120–160°C, the main reaction is the formation of the p-p methylene group. From 160°C to 190°C, the main reactions are the breaking of the ether bond, the formation of the carbonyl group and the propyl bridge. Above 190°C, the main reactions are polycondensation reaction among phenolic hydroxyl groups, and the formation reaction of carbonyl groups. The ether bond breaks completely above 230°C. This work provides a new method to investigate the curing mechanism. It is a benefit for the rational design of the curing process of phenolic resin-based composites.